Bulked segregant RNA-seq reveals complex resistance expression profile to powdery mildew in wild emmer wheat W762 - Qian, Zejun; Liu, Ruishan; Liu, Xueqing; Qie, Yanmin; Wang, Jiangchun; Yin, Yan; Xin, Qingguo; Yu, Ningning; Zhang, Jiadong; Li, Yaoxue; Li, Jiatong; Dai, Yintao; et al. (Frontiers in Plant Science, 2024)
Powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is one of the most destructive fungal diseases threatening global wheat production. Exploring powdery mildew resistance (Pm) gene(s) and dissecting the molecular mechanism of the host resistance are critical to effectively and reasonably control this disease. Durum wheat (Triticum turgidum L. var. durum Desf.) is an important gene donor for wheat improvement against powdery mildew. In this study, a resistant durum wheat accession W762 was used to investigate its potential resistance component(s) and profile its expression pattern in responding to Bgt invasion using bulked segregant RNA-Seq (BSR-Seq) and further qRT-PCR verification. Genetic analysis showed that the powdery mildew resistance in W762 did not meet monogenic inheritance and complex genetic model might exist within the population of W762 × Langdon (susceptible durum wheat). After BSR-Seq, 6,196 consistently different SNPs were called between resistant and susceptible parents and bulks, and among them, 763 SNPs were assigned to the chromosome arm 7B. Subsequently, 3,653 differentially expressed genes (DEGs) between resistant and susceptible parents and bulks were annotated and analyzed by Gene Ontology (GO), Cluster of Orthologous Groups (COG), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. The potential regulated genes were selected and analyzed their temporal expression patterns following Bgt inoculation. As a result, nine disease-related genes showed distinctive expression profile after Bgt invasion and might serve as potential targets to regulate the resistance against powdery mildew in W762.